2019
DOI: 10.1136/bmjopen-2018-025036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of point-of-care C reactive protein in ambulatory care: a systematic review and meta-analysis

Abstract: ObjectiveThe aim of this review was to collate all available evidence on the impact of point-of-care C reactive protein (CRP) testing on patient-relevant outcomes in children and adults in ambulatory care.DesignThis was a systematic review to identify controlled studies assessing the impact of point-of-care CRP in patients presenting to ambulatory care services. Ovid Medline, Embase, Cochrane Database of Systematic Reviews, Cochrane CENTRAL, DARE, Science Citation Index were searched from inception to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 60 publications
1
65
1
1
Order By: Relevance
“…One review focused on RTIs in primary care, but the results published six years ago were limited by a small number of studies of generally small samples that included mostly adults [ 25 ]. The second review with a broader scope included all acute infections presenting to ambulatory care [ 26 ]. We performed a systematic review to assess the evidence on the clinical effectiveness of CRP-POCT compared with usual care in reducing antibiotic prescribing for RTIs in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…One review focused on RTIs in primary care, but the results published six years ago were limited by a small number of studies of generally small samples that included mostly adults [ 25 ]. The second review with a broader scope included all acute infections presenting to ambulatory care [ 26 ]. We performed a systematic review to assess the evidence on the clinical effectiveness of CRP-POCT compared with usual care in reducing antibiotic prescribing for RTIs in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…A large study in Vietnam showed a reduction of antibiotic use after CRP testing for nonsevere acute RTIs in adults as well as in children [26]. In the European ambulatory care setting, there is evidence that CRP testing can reduce immediate antibiotic prescription in children when appropriate guidance is provided to the healthcare professional [27,28]. A randomised controlled trial from Switzerland studied PCT-guided treatment, but found no effect on antibiotic prescription rates [29].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review forms part of a series of analyses from a larger overall review (in progress) which will assess the overall quantitative impact of all POCTs in ambulatory care, further subgroup analyses on C-reactive protein (CRP)13 and influenza14 have already been published.…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review forms part of a series of analyses from a larger overall review (in progress) which will assess the overall quantitative impact of all POCTs in ambulatory care. This main search was originally performed on 19 November 2015 and then updated on 21 March 2017, following this subgroup analyses on CRP13 and influenza14 were published. Studies based in resource poor settings form another subgroup analyses from the overall review and will also be published separately.…”
Section: Introductionmentioning
confidence: 99%